Integral Functionals of the Gasser–Muller Regression Function - Arabidze, D.; Babilua, P.; Nadaraya, E.; Sokhadze, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
For integral functionals of the Gasser–Muller regression function and its derivatives, we consider the plug-in estimator. The consistency and asymptotic normality of the estimator are shown.